Victimisation and justice in intercultural context in Serbia - Nikolić-Ristanović Vesna; Ćopić Sanja; Petrović Nikola M.; Šaćiri Bejan (Temida, 2015)
During 2013, within the ALTERNATIVE project, Victimology Society of Serbia conducted an empirical research study with the aim to find out how people from three multiethnic communities in Serbia deal with interethnic conflicts in their everyday life and to identify both problems and positive experiences in solving them. It also analysed how victims are treated, how the security and justice are perceived by the citizens, and what is the place of restorative approaches in dealing with conflicts and security. The research was conducted in Bačka Palanka, Bač, Prijepolje and Medveđa. It consisted of qualitative and quantitative part, and it had a strong action dimension. After a brief description of the research methodology, we present main research findings related to the conflicts that have been evolving since 1990 between members of different ethnic groups in three multiethnic communities in Serbia, focusing on the prevalence and characteristics of victimisation and respondents’ notions of justice, i.e. mechanisms suitable to achieve justice in the concrete cases of victimisation they experienced. In the conclusion we point out that respondents attribute high relevance to both formal and informal restorative approaches, suggesting the need of citizens in general, and victims in particular to actively participate in the process of conflict transformation and prevention of further victimisations. [The research leading to these results has received funding from the European Union’s Seventh Framework Programme (FP7-SEC-2011-1) under grant agreement n°285368]